Pengaruh Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Mediasi Di PT Kaltim Prima Coal - Marsela, Putri; Ayu Setyaning, Alldila Nadhira (Universitas Hamzanwadi, 2024)
This study aims to understand the impact of Organizational Culture and Work Compliance on Employee Performance mediated by Work Motivation at PT Kaltim Prima Coal. The research employs a quantitative method, with a population of 206 employees at PT Kaltim Prima Coal. Purposive sampling method was used, involving 136 respondents in this study. Data were collected through the distribution of questionnaires using a Likert Scale ranging from 1 to 5, and SPSS was used for data analysis. The findings of this study indicate that (1) Organizational Culture has a positive impact on Work Motivation, (2) Work Compliance has a positive impact on Work Motivation, (3) Organizational Culture has a negative impact on Employee Performance, (4) Work Compliance has a positive impact on Employee Performance, (5) Employee Performance is positively influenced by Work Motivation, (6) Through Work Motivation, Organizational Culture positively impacts Employee Performance, and (7) Through Work Motivation, Work Compliance positively impacts Employee Performance.